Teen Titans go!. Volume 4, Smells like Teen Titans spirit - Morrissey, Paul (DC Comics, 2017)
The Teen Titans find themselves in a new set of adventures when Beast Boy develops the power to smell the future, and just may in the process fulfill an ancient prophecy--then, the Titans have to babysit an infant Superman.